Fascinating landscapes of “Hypnerotomachia Poliphili”: source for research of plant diversity, horticulture and culture - Sophia Rhizopoulou (Acta Horticulturae, 2017)
Hypnerotomachia Poliphili” (HP) is a literary source of semi-natural and human-induced landscapes that centred on seductive environmental attributes, such as gardens, groves, pergolas and dispersed ancient ruins, which represent knowledge derived from the tradition and experience of ages. HP is the short title of one of the most influential books of the Renaissance (the first edition was published by Aldus Manutius in Venice, in 1499); it is the story of a man (Poliphilos), who falls asleep and dreams of traversing landscapes and gardens containing plants, ancient ruins and allegorical figures, in order to be reunited with his beloved (Polia). Interest in this novel has been revived, due to substantial influence on landscape and garden design. In this study, attention has been given to the botanical section preserved in the text. Paying attention to narratives provides a source for (re)considering conceptions of landscapes, nature and culture, wild and domesticated plant life. Arboreal and bush plants here quoted disclose aspects of plant diversity and ecophysiology; among a large number of plant taxa, roses, myrtle, pines, cypresses, laurels, acanthus, oaks, olive trees, juniper, ivy, thyme, oregano, violets, wormwood and cyclamens were the most frequently cited. Also, the seasonality of Mediterranean landscapes, indicated by flowering and fruit-bearing indigenous plants, can be traced through textual passages. Its wood-engraved illustrations of portrayed landscapes and botanic sketches (e.g. ferns, palms, oaks, cypresses, box trees and foliage of laurel, acanthus, grapevine and ivy) constitute evidence for both plant diversity and natural history, at the end of the fifteenth-century.